FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN MAHASISWA MEMILIH JURUSAN PAUD FKIP UNRI - Sandi Sandi; Achmad Hidir (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine what factors that are influencing students in choosing Department of Early Childhood Education at Faculty of Teacher Training and Education in Riau University. The independent variables of this study are actors, resources and norms, and the dependent variable is students’ decision in choosing Department of Early Childhood Education at Faculty of Teacher Training and Education in Riau University. The data used in this study is primary data collected directly from students of Department of Early Childhood Education at Faculty of Teacher Training and Education in Riau University. The Analytical method used is quantitative method and analyzed by correlation using SPSS 22 for Windows. The result of data analysis shows resources have an insignificant negative effect with a very low level of correlation to students’ decisions to choose Department of Early Childhood Education at Faculty of Teacher Training and Education in Riau University, meanwhile norms have a significant positive effect with a low level of correlation to students’ decision to choose Department of Early Childhood Education at Faculty of Teacher Training and Education in Riau University